Young women farmers in Indonesia: at the intersection of class, generation and gender - Ambarwati, Aprilia (Akatiga Foundation, 2019)
Presented by Aprilia Ambarwati (Akatiga Foundation), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.